3(5c-6)=5(3c+6)

Simple and best practice solution for 3(5c-6)=5(3c+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5c-6)=5(3c+6) equation:



3(5c-6)=5(3c+6)
We move all terms to the left:
3(5c-6)-(5(3c+6))=0
We multiply parentheses
15c-(5(3c+6))-18=0
We calculate terms in parentheses: -(5(3c+6)), so:
5(3c+6)
We multiply parentheses
15c+30
Back to the equation:
-(15c+30)
We get rid of parentheses
15c-15c-30-18=0
We add all the numbers together, and all the variables
-48!=0
There is no solution for this equation

See similar equations:

| a+7=2a−8. | | 0.5(9x+18)=-1.5(5x)-2(3+4.5) | | (3x+15)+(x+25)=180 | | 0.5(4x+2)=-2(2x+3)-11 | | -36=-6(f+-8) | | 7x+6(x+8)=22 | | 9=3/5u | | 4(f-68)=68 | | 82-v=295 | | 4x-7x+21=36 | | 4w+4(w-7)=20 | | 6u/5=30 | | (x+4)(5x+1)=0 | | 0.5(9x+18)=–1.5(5x)–2(3x+4.5) | | 9=18-n | | 3(5.30g+50)=55.20 | | 2w=14/9 | | 3(2+x)-11=7 | | -14=2(y+2)+7y | | z-17=3 | | 4x-6-2x=7x-2-3x | | s/54=6 | | 10p-6p=3p-5 | | 3=c+2/4 | | 14=5(u-8)+4 | | 3x-6x+7=-2 | | 3(x-4)=2x=3x-37 | | t-19=7 | | 4x-3=5-(x+3) | | P-3+3p=9 | | 2(v+3)+5v=34 | | 2x3-20=0 |

Equations solver categories